The reality of the use of technology in the teaching of mathematics for the primary school in the city of Arar from the point of view of teachers and teachers - Al-Anzi, Abdul Aziz bin Rawaf; Al-Massad, Ahmed bin Zaid (Journal of Educational and Psychological Sciences, 2018)
The current research aims to identify the reality of the use of technology in teaching mathematics for the primary stage in the schools of Arar، from its teacher’s point of view; the researcher used the descriptive method for its relevance to the current research. The research population is composed of all mathematics teachers in Arar city in (1438-1439H). The objective of the research was verified through the analytical description of the response of (170) teachers of mathematics for elementary teachers in the schools of Arar city. The research reached the following main results: 1 - The availability of tools and equipments in the classroom environment and school that ensure the use of technology in teaching mathematics was high. 2 - The extent of the use of technology in teaching mathematics for the primary school in the city of Arar with an average degree of low applicability. The obstacles of the use of technology in teaching of mathematics for the primary schools in Arar city were low. As the results of the study indicate that there are no statistically significant differences in all fields according to the variable years of experience، and gender The study concluded with recommendations such as: The need to employ methods of teaching activity-based mathematics and interaction with educational tools، especially primary school students، as well as the preparation of training and guidance programs for mathematics teachers to learn how to use and employ modern techniques in teaching mathematics.